2017
DOI: 10.1186/s13075-017-1309-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10-producing LAG3+ regulatory T cells are associated with disease activity and abatacept treatment in rheumatoid arthritis

Abstract: BackgroundRegulatory T cells (Tregs) play a role in the suppression of inflammation in autoimmune diseases, and lymphocyte activation gene 3 (LAG3) was reported as a marker of interleukin (IL)-10-producing Tregs. We aimed to clarify the function of human IL-10-producing CD4+CD25−LAG3+ T cells (LAG3+ Tregs) and their association with rheumatoid arthritis (RA).MethodsLAG3+ Tregs of human peripheral blood mononuclear cells (PBMCs) were cultured with B cells and follicular helper T cells to examine antibody suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 45 publications
3
33
0
1
Order By: Relevance
“…Response to treatment with tocilizumab, an IL-6 receptor inhibitor, is associated with higher baseline frequencies of natural killer (CD3 − CD56 + ) cells [80] and higher increases in the frequencies of T REG cells in the periphery [81]. A case-control study of RA patients and healthy controls demonstrated that IL-10+ producing LAG3 + T REG cells are specifically increased after treatment with abatacept, and that the magnitude of this increase is correlated with the strength of response [82]. Immunoprofiling studies have also revealed changes in the function of lymphocyte populations in response to therapy: for example, RA patients who respond well to anti-TNF treatment have higher production of GM-CSF from T cells [83].…”
Section: Identifying Biomarkers Through Cell Phenotypingmentioning
confidence: 99%
“…Response to treatment with tocilizumab, an IL-6 receptor inhibitor, is associated with higher baseline frequencies of natural killer (CD3 − CD56 + ) cells [80] and higher increases in the frequencies of T REG cells in the periphery [81]. A case-control study of RA patients and healthy controls demonstrated that IL-10+ producing LAG3 + T REG cells are specifically increased after treatment with abatacept, and that the magnitude of this increase is correlated with the strength of response [82]. Immunoprofiling studies have also revealed changes in the function of lymphocyte populations in response to therapy: for example, RA patients who respond well to anti-TNF treatment have higher production of GM-CSF from T cells [83].…”
Section: Identifying Biomarkers Through Cell Phenotypingmentioning
confidence: 99%
“…These findings are supported by LAG-3 expression, which showed no difference between the groups ( Figure 1B). The activation gene (LAG3) has been reported as a marker of IL-10 producing Treg [27]. Taking these findings together suggests that impaired Treg function in AA is mainly due to a defect in cell-to-cell contact and CD39-mediated suppressive machinery and not in cytokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to murine LAG3 + Tregs, these human LAG3 + T cells produce large amounts of IL‐10 in response to TCR stimulation and suppress humoral immunity. When the frequency of LAG3 + Tregs in the peripheral blood of rheumatoid arthritis patients was examined, it was lower in patients with rheumatoid arthritis, especially those with higher disease activity . Further studies are required to evaluate the role of human LAG3 + Tregs in other autoimmune diseases.…”
Section: Role Of the Egr2 Gene In Lag3+ Tregsmentioning
confidence: 99%